Determinants of parental seasonal influenza vaccine hesitancy in the Eastern Mediterranean region: A cross-sectional study - Fadl, Noha; Al Awaidy, Salah T.; Elshabrawy, Abdelhamid; Makhlouf, Mona Sayed Aly Hassan; Ibrahim, Sarah Assem; Abdel-Rahman, Suzan; Tookhy, Nazir Ahmad; Alsalmani, Abdullah; Al-Saeedi, Mays; Al-Sawalha, Ibrahim; El-Din, Mohammad Amin Aly; Saad, Janet; et al. (Frontiers in Public Health, 2023)
Background Seasonal influenza vaccine can reduce the risk of influenza-associated hospitalizations and deaths among children. Given that parents are the primary decision makers, this study examined the parental attitude toward childhood influenza vaccine and identified determinants of vaccine hesitancy (VH) in the Eastern Mediterranean region (EMR). Methods A cross-sectional study was conducted using an anonymous online survey in 14 EMR countries. Parents of children aged 6 months to 18 years were included. The Parent Attitude about Childhood Vaccines (PACV) was used to assess VH. Chi square test and independent t-test were used to test for association of qualitative and quantitative variables, respectively. A structural equations model (SEM) was used to identify direct and indirect determinants of parental VH. Results Almost half of the parents were hesitant about vaccinating their children against influenza (50.8%). Parental VH was significantly higher among older mothers (37.06 ± 8.8 years, p = 0.006), rural residents (53.6%, p < 0.001), high-income countries residents (50.6%, p < 0.001), and mothers with higher educational levels (52.1%, p < 0.001). Parents of school-aged children (5–9 years) (55.6%, p < 0.001), children free from any comorbidities (52.5%, p < 0.001), children who did not receive routine vaccination at all (51.5%, p = 0.03), children who were not vaccinated against COVID-19 (54.3%, p < 0.001), in addition to parents who were not vaccinated against influenza (57.1%, p < 0.001) were significantly associated with increased likelihood of VH. Parents who were depending on healthcare provider as a source of information regarding vaccines were less likely to report VH (47.9%, p < 0.001), meanwhile those who used social media as their source of health information showed a significantly higher VH (57.2%, p < 0.001). The SEM suggested that mother’s age, residence, country income level, child gender, total number of children and source of information regarding vaccines had a direct effect on VH. Meanwhile, parents vaccinated against influenza, children completely or partially vaccinated with routine vaccines and children vaccinated against Coronavirus disease 2019 (COVID-19) had an indirect effect on VH. Conclusion A high proportion of included parents were hesitant to vaccinate their children against seasonal influenza. This attitude is due to many modifiable and non-modifiable factors that can be targeted to improve vaccination coverage.